Pilihan Tempat Belanja Ibu Rumah Tangga Perdesaan di Indonesia - Permana, I Putu Widi; Tisnawati, Ni Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 8, Agustus 2016 (pp. 846-901), 2016)
Increasing the number of modern markets affect the sustainability of traditional markets that can not compete with modern markets due to the facilities in the modern market is already very convenient. Traditional markets became a historical heritage and the persistence of economic class divisions down to strive so that the need for efforts to safeguard the future sustainability of traditional markets. The variables contained in socioeconomic factors are income, assets, family size and age of the mother's decision of rural households will shop at traditional markets and modern. Data analysis technique used is Binary Logistic. The results showed that rural housewives decision to shop at traditional markets in the amount of 97.9 percent. Variable income, assets, family size and age have a significant effect on the decision of rural housewives to shop at traditional markets in the amount of 11, 103. The income variable significant effect on rural housewives decision to shop at traditional markets of -1.595, variable influential asset significant of 0.740, a variable number of families have a significant effect of 0.075 and the age variable significant influence amounted to 0.052.
Keywords: Decision Housewife Rural; Income; Consumption; Age